Impact of External Cultural Values on the Financial Performance of Listed Companies on the Ho Chi Minh Stock Exchange (Hose) Vietnam - Chau Thi Le Duyen; Nguyen Thanh Liem; Le Thi Ngoc Anh; Nguyen Pham Tuyet Anh (Kurdish Studies, 2024)
The research findings contribute to studies on external commitment values in particular, and the overall impact of organizational culture on financial performance. This provides Vietnamese businesses listed on the HOSE stock exchange and all businesses in Vietnam with additional insights into the relationship between corporate culture and financial performance. After collecting and analyzing data from 108 observations, the research results indicate that five external commitment values affect the financial performance of companies listed on the HOSE. These include four positively impacting values: Quality-Innovation, Product, Social Responsibility, and Financial, and one negatively impacting value: Economic.